Postoperative Outcomes Analysis After Pancreatic Duct Occlusion: A Safe Option to Treat the Pancreatic Stump After Pancreaticoduodenectomy in Low-Volume Centers - Giuliani, Antonio; Avella, Pasquale; Segreto, Anna Lucia; Izzo, Maria Lucia; Buondonno, Antonio; Coluzzi, Mariagrazia; Cappuccio, Micaela; Brunese, Maria Chiara; Vaschetti, Roberto; Scacchi, Andrea; Guerra, Germano; Amato, Bruno; et al. (Frontiers in Surgery, 2021)
Background: Surgical resection is the only possible choice of treatment in several pancreatic disorders, included periampullar neoplasms. The development of a postoperative pancreatic fistula (POPF) is the main complication. Despite three different surgical strategies have been proposed - pancreatojejunostomy, pancreatogastrostomy and pancreatic duct occlusion (DO) - none of them has been clearly validated to be superior. The aim was to analyze the post-operative outcomes after DO. Methods: We retrospectively reviewed 56 consecutive patients underwent Whipple’s procedure from January 2007 to December 2014 in a tertiary Hepatobiliary Surgery and Liver Transplant Unit. After pancreatic resection in open surgery, we performed DO of the Wirsung duct with Cyanoacrylate glue independently from the stump characteristics. The mean follow-up was 24.5 months. Results: 29 (60.4%) were males and 19 were (39.6%) females with a mean age of 62.79 (SD ± 10.02) years. Surgical indications were in the 95% of cases malignant diseases. The incidence of POPF after DO was 31 (64.5%): 10 (20.8%) patients had a Grade A fistula, 18 (37.5%) Grade B fistula, and 3 (6.2%) Grade C fistula. No statistical differences were demonstrated in development of POPF according to pancreatic duct diameter groups (p-value = 0.2145). Nevertheless, POPF rate was significantly higher in the soft pancreatic group (p-value = 0.0164). The mean operative time was 358.12 min (SD ± 77.03, range: 221-480 min). Hospital stay was significantly longer in patients who developed POPF (p-value <0.001). According to the Clavien-Dindo (CD) classification, 7/48 (14.58%) patients were classified as CD III-IV. At the last follow-up, 27 of the 31 (87%) patients were alive. Conclusions: DO can be proposed as a safe alternative to pancreatic anastomosis especially in low/medium volume centres in selected cases at higher risk of clinically relevant POPF.